2015
DOI: 10.1016/j.ijfatigue.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict S–N curves for surface and subsurface crack initiations in different environmental media

Abstract: a b s t r a c tThe influence of environmental media on crack propagation of a structural steel at high-cycle and veryhigh-cycle fatigue (VHCF) regimes was investigated with the fatigue tests in air, water and 3.5% NaCl aqueous solution. The fatigue strength in water and 3.5% NaCl solution is significantly decreased and the cracking morphology due to different driving forces is presented. A model is proposed to explain the influence of environmental media on fatigue life, which reflects the variation of fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…However, it is widely accepted that corrosion fatigue crack initiation points are due to surface defects (such as corrosion pits and voids) of aluminium alloys caused by NaCl aqueous solutions by previous literature. 10,[13][14][15]27,28 In addition, effects of second cracks of high-strength aluminium alloy, 7475-T7351 and 7075-T651, as shown in Fig. 2a and b, and voids of high-ductility aluminium alloys, LY12-CZ and 2024-T4, as shown in Fig.…”
Section: R E S U L T S a N D Discussion Smentioning
confidence: 94%
See 1 more Smart Citation
“…However, it is widely accepted that corrosion fatigue crack initiation points are due to surface defects (such as corrosion pits and voids) of aluminium alloys caused by NaCl aqueous solutions by previous literature. 10,[13][14][15]27,28 In addition, effects of second cracks of high-strength aluminium alloy, 7475-T7351 and 7075-T651, as shown in Fig. 2a and b, and voids of high-ductility aluminium alloys, LY12-CZ and 2024-T4, as shown in Fig.…”
Section: R E S U L T S a N D Discussion Smentioning
confidence: 94%
“…In recent years, many studies have focused on the fatigue behaviour of Al alloys in the corrosive environment. 14 Li et al 15 estimated the effect of pre-corrosion states on the fatigue microcrack initiation and early stage propagation behaviour of 6151-T6 aluminium alloy based on scanning electron microscopy (SEM) in situ observation. Hui et al 16 and Qian et al…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that a fatigue crack always initiates from the interior of specimen for VHCF, 9,10 which is different from the surface crack initiation mechanism for low-cycle fatigue and high-cycle fatigue. 11,12 In addition, the unique influences of stress ratio, [13][14][15] strength level, 16 loading frequency, 16,17 specimen size 18,19 and environmental condition 20,21 on the behavior of VHCF have been reported. However, the theories of physics and mechanics for the explanation of VHCF experiments still need further development.…”
Section: Introductionmentioning
confidence: 99%
“…For high-strength steels, cracks are prone to initiate at specimen subsurface or interior [9][10][11][12][13] in VHCF regime, and a distinct crack initiation feature of ''fish-eye" morphology embracing a region of ''fine-granular-area (FGA)" usually presents at fracture surface. Another typical feature of VHCF behavior for highstrength steels is that the S-N curve is a stepwise or duplex shape [14][15][16][17][18][19][20][21] with regard to surface-induced and interior-induced crack initiation, respectively. Bathias and Paris [22] investigated several high-strength steels via ultrasonic fatigue test technique and revealed that subsurface crack initiated from either nonmetallic inclusions or other microstructural inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…Their result demonstrated that the formation of FGA is responsible for a majority part of total fatigue life and the fraction of fatigue life contributed by FGA is beyond 95% in VHCF regime. Further, a D ⁄ parameter has been proposed to discuss the competition of crack initiation from the surface and from the interior of specimen [20,21], which gave an explanation for the preference of fatigue crack initiation either from the surface or from the interior of specimen.…”
Section: Introductionmentioning
confidence: 99%